2009
DOI: 10.1631/jzus.b0820384
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in the effect of daytime sleep on declarative memory for pictures

Abstract: Abstract:Objective: To investigate gender difference in the effects of daytime sleep on item and source memories, which are dissociable elements of declarative memory, and the effects of sleep on recollection and familiarity, which are two processes underlying recognition. Methods: Participants saw a series of pictures with either blue or red background, and were then given a pretest for item and source memories. Then males and females respectively were randomly assigned either to a wake or a sleep condition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Many aspects of microexpressions need to be elucidated in the future including the lower limit, individual differences in expression and recognition of microexpressions (Bond and DePaulo, 2008;O′Sullivan et al, 2009;Wang and Fu, 2009;Warren et al, 2009), effective methods of training and the retention of training effects (Hurley, 2010;Matsumoto and Hwang, 2011), and automatic brief facial expression analysis systems (Polikovsky et al, 2010;Wu et al, 2010). As for individual differences, in groups closely related to deception detection, such as crime interrogators, national security personnel, visa interviewers, sales personnel, negotiators, and mental health professionals, the expression and recognition of microexpressions might not be the same as for other people.…”
Section: Discussionmentioning
confidence: 99%
“…Many aspects of microexpressions need to be elucidated in the future including the lower limit, individual differences in expression and recognition of microexpressions (Bond and DePaulo, 2008;O′Sullivan et al, 2009;Wang and Fu, 2009;Warren et al, 2009), effective methods of training and the retention of training effects (Hurley, 2010;Matsumoto and Hwang, 2011), and automatic brief facial expression analysis systems (Polikovsky et al, 2010;Wu et al, 2010). As for individual differences, in groups closely related to deception detection, such as crime interrogators, national security personnel, visa interviewers, sales personnel, negotiators, and mental health professionals, the expression and recognition of microexpressions might not be the same as for other people.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the interfering effect between the two memory systems during the day, and their independence during sleep, were not considered in the study of Genzel et al [34]. In a second study, Wang et al [37] investigated the effects of daytime sleep on episodic declarative memory, and recollection and familiarity in women and men groups. They reported that a nap may contribute to the retention of the contextual aspect of episodic memory rather than the item information itself in women, while nap increased familiarity in men.…”
Section: Introductionmentioning
confidence: 99%
“…Such gender difference may be linked with different memory traces resulting from different encoding strategies, as well as different electrophysiological changes during daytime sleep. Finally, Wang et al [37] concluded that women are more likely to be affected by the influences of daytime sleep than men. Together, these findings provide insights in the characterization of the consolidation process with respect to gender, even though knowledge on this issue is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, gender and age did not influence cognitive performance after a nap. However, literature suggested sex differences in benefits of daytime sleep, for example, greater benefits on memory for women [ 100 ]. A lab environment does not completely duplicate the real world.…”
Section: Discussionmentioning
confidence: 99%